2021
DOI: 10.1007/s13555-021-00535-7
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Herpes Zoster in Adult Patients with Underlying Conditions: Analysis of German Claims Data, 2007–2018

Abstract: Introduction Several chronic underlying conditions (UCs) are known to be risk factors for developing herpes zoster (HZ) and to increase the severity of HZ and its risk of recurrence. The aim of this study was to investigate the incidence and recurrence of HZ in adult patients with one or multiple UCs. Methods A retrospective cohort study based on claims data representing 13% of the statutory health insurance population from 2007 to 2018 in Germany was performed. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 53 publications
5
40
0
1
Order By: Relevance
“…We defined herpes zoster using EHR, but people with more comorbidities may visit their primary care physicians more frequently. Thus, herpes zoster among these people is more likely to be diagnosed, while mild shingles among a younger or healthier population might not be noticed (22). In our study population, although the proportions of people with diabetes and chronic obstructive pulmonary disease were slightly higher in the vitamin D deficiency group, the overall distributions of comorbidities and immunosuppression were similar across different vitamin D statuses.…”
Section: Strengths and Limitationsmentioning
confidence: 52%
See 1 more Smart Citation
“…We defined herpes zoster using EHR, but people with more comorbidities may visit their primary care physicians more frequently. Thus, herpes zoster among these people is more likely to be diagnosed, while mild shingles among a younger or healthier population might not be noticed (22). In our study population, although the proportions of people with diabetes and chronic obstructive pulmonary disease were slightly higher in the vitamin D deficiency group, the overall distributions of comorbidities and immunosuppression were similar across different vitamin D statuses.…”
Section: Strengths and Limitationsmentioning
confidence: 52%
“…HZ was defined using EHRs, but people with a greater number of comorbidities may visit their primary care physicians more frequently than people without underlying chronic diseases; as such, HZ in these people is more likely to be diagnosed, whereas mild shingles among a younger or healthier population might not be noticed. 23 In the study population, although the proportions of people with certain conditions were slightly higher in those who were deficient in vitamin D, the overall distributions of comorbidities and immunosuppression were similar across different vitamin D statuses. Any ascertainment bias in the study presented here should be non-differential.…”
Section: Discussionmentioning
confidence: 76%
“…There are conflicting findings regarding the use of steroids in asthma patients and their association with HZ development. Several studies have found that when compared to those who did not have a regular controller, asthma patients who received daily inhaled corticosteroid (ICS) or systematic corticosteroid treatment had a slightly higher risk of HZ 25,26,29,32 . The same results were obtained when a noncorticosteroid immunosuppressive agent was used 26 .…”
Section: Asthma and Hzmentioning
confidence: 92%
“…21,22 Based on these observations, several studies have reported an increased susceptibility to viral infections, including in nonrespiratory sites, in asthmatic patients. 19,23 4 | ASTHMA AND HZ Association between asthma and skin infection, specifically HZ, has been proposed in several studies, both in the adult [24][25][26][27][28][29] and pediatric [30][31][32] populations. In the adult populations, the prevalence of HZ sufferers who had a history of bronchial asthma ranges from 7.1% to 23% 24,26 while, in the pediatric population is around 7.7% to 28.1%.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation